2021
DOI: 10.3390/ijerph18126342
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior and Well-Being of Adults with Physical Disabilities and/or Chronic Diseases during the First Wave of the COVID-19 Pandemic: A Rapid Review

Abstract: Background: People with physical disabilities and/or chronic diseases report lower levels of physical activity and well-being than the general population, which potentially is exacerbated through the COVID-19 pandemic. This study explored the international literature on physical activity, sedentary behavior and well-being in adults with physical disabilities and/or chronic diseases during the first wave of the pandemic. Method: In a rapid review, we included studies reporting on physical activity, sedentary be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…Another review study investigating adults with physical disabilities and/or chronic diseases found an increase in SB during the first wave of COVID-19 in almost every examined case [81].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another review study investigating adults with physical disabilities and/or chronic diseases found an increase in SB during the first wave of COVID-19 in almost every examined case [81].…”
Section: Discussionmentioning
confidence: 95%
“…In a mini-review [80], the authors reported a significant reduction of PA levels among university students compared to pre-lockdown values. Moreover, another review study investigating adults with physical disabilities and/or chronic diseases found a decrease in PA during the first wave of COVID-19 in almost every examined study [81].…”
Section: Discussionmentioning
confidence: 97%
“…Reflecting existing evidence of a negative impact on physical activity during the pandemic in this group, 19 36 participants with disabilities were around 3.5 times more likely to not exercise at all than participants with no disabilities. This may reflect challenges imposed by lockdown restrictions including disruption to public transport and reduced access to professional and social support for attending gyms, 36 and existing barriers to physical activity. 19 37 The most common types of disability in this sample were visual impairment/blindness, disability affecting mobility and mental health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence concerning the detrimental physical and mental effects of the pandemic [ 1 , 2 ], including on athletic populations [ 3 , 4 ]. The detrimental effects of lockdowns appear to vary among individuals [ 5 ]. For example, para- and able-bodied athletes require differing levels of support and equipment to train effectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%